Application of coconut battery waste to graphic as an alternative electrode on primary battery cells - Siburian, Rikson; L Raja, Saur; Supeno, Minto; Simanjuntak, Crystina (Talenta Publisher, 2019)
Coconut shell is one of the potential biomass as carbon sources. Coconut shell is converted to charcoal through the carbonization process. The potential of charcoal from coconut shells can be synthesized into graphene. Graphene is a derivative of one of the carbon allotropes, namely graphite, where carbon is in the form of thin plates with sp2 orbitals arranged hexagonally. The process of making graphene which is coconut shell dried in the sun then pyrolysis into charcoal then mixed with activated carbon as a reducing agent at 600 ° C for 1 hour to produce graphene. The graphene produced is characterized by X-Ray Diffraction (XRD), Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX). The results by XRD analysis showed the resulting peaks were not sharp and slightly widened at the diffraction peaks at 24 ° and 44 °. The results of SEM-EDX analysis at 4000x magnification show the surface size and shape of the structure that is smaller, thinner and reduced buildup on the graphene structure. graphene that has been successfully synthesized was tested on a coin battery. The coin battery cathode which was replaced with graphene succeeded in turning on the light.